2009
DOI: 10.1121/1.3179666
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language categorization of French and German vowels by naïve American listeners

Abstract: American English (AE) speakers' perceptual assimilation of 14 North German (NG) and 9 Parisian French (PF) vowels was examined in two studies using citation-form disyllables (study 1) and sentences with vowels surrounded by labial and alveolar consonants in multisyllabic nonsense words (study 2). Listeners categorized multiple tokens of each NG and PF vowel as most similar to selected AE vowels and rated their category "goodness" on a nine-point Likert scale. Front, rounded vowels were assimilated primarily to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Phonetic context may affect vowel perception ͑Bohn and Steinlen, 2003͒, as well. Strange et al ͑2009͒ found effects of consonantal context and speaking style ͑i.e., citation form disyllables vs sentences͒ on assimilation of French and German vowels in sentences by naïve AE listeners. For example, PF /y/ was more often assimilated to AE /u/ in alveolar ͑94%͒ than in bilabial ͑74%͒ context.…”
Section: The Discrimination Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phonetic context may affect vowel perception ͑Bohn and Steinlen, 2003͒, as well. Strange et al ͑2009͒ found effects of consonantal context and speaking style ͑i.e., citation form disyllables vs sentences͒ on assimilation of French and German vowels in sentences by naïve AE listeners. For example, PF /y/ was more often assimilated to AE /u/ in alveolar ͑94%͒ than in bilabial ͑74%͒ context.…”
Section: The Discrimination Experimentsmentioning
confidence: 99%
“…For example, Best et al ͑2001͒ designated a nonnative speech sound as "uncategorized" if a listener's orthographic transcription of the sound suggested one that fell between two or more native English categories. Other researchers ͑e.g., Strange et al, 2009͒ have used inter-and intra-subject consistencies of categorization as indications of whether sounds are uncategorized. Harnsberger ͑2001͒ determined a speech sound to be uncategorized when its top label represented less than 90% of a group's responses.…”
Section: Introductionmentioning
confidence: 99%
“…Following standard methods in the field (Gordon, 2008(Gordon, , 2011Levy, 2009;Morrison, 2003;Nishi et al, 2008;Strange et al, 2004Strange et al, , 2009Vasiliev, 2013), we define cross-language similarity by means of previous results of perceptual assimilation tasks in which listeners are presented with nonnative sounds and are asked to state which L1 sound they are most similar to, and to rate them as exemplars of the L1 categories.…”
Section: The Role Of Assimilation Patterns In the Acquisition Of Spanmentioning
confidence: 99%
“…17 French vowels /e/ and /E/ are difficult to discriminate by listeners of French dialects that have neutralized this context 3,4 /e-E/ are sometimes confused for each other by English listeners, especially in open-syllable context, 5 and French /E/ is sometimes perceived as most similar to English /e/. 18 Despite the fact that /e/ and /E/ are phonemic in both English and French, French /e/ and /E/ tend to be spectrally higher than in English 14 and /E/ can occur word-finally in French, but not in English. Finally, the speakers in the present study produced /E/ with a duration that was longer than /e/ when preceded by a stop, or roughly equivalent when preceded by /Ò/.…”
Section: Discussionmentioning
confidence: 99%